Migration and the City: the Chinese (and Investment Visas) in the Portuguese Press - Santos, T. R.; Castro, P.; Guerra, R. (The Migration Conference, 2018)
We live in a world where different groups of different socio-economic conditions increasingly move around to study, work, settle short or long-term, or invest. These different groups see their conditions for acceptance and integration shaped by many factors, including their different relationships with the institutions and legal frameworks of the host society (Fonseca, Caldeira, & Esteves, 2002). These differences are particularly relevant when incentives for settlement vary depending on socio-economic status (Howarth & Andreouli, 2013), as it is the case of Portugal, where residency permits for economic investment now exist. The Investment Visa (IV) is changing the notion of ‘the spatially bounded citizen’ (Ley, 2003), adding a new layer of understanding to citizenship – one in which the goals and values of economic investment are privileged. In Portugal, the Chinese were already an important migrant group, and are now also a sizable percentage of IV holders, investing, to a big extent, in the city of Lisbon. Aiming at examining how these more varied Chinese communities are being presented to the Portuguese public sphere through the press – exploring also the institutions and social meanings they are associated with - two widely-read newspapers, a quality (Público) and a popular (Correio da Manhã) one, were analyzed. A total of 532 articles (Público n= 287 and Correio da Manhã n= 238) were collected using the keywords ‘Chinese’ and ‘Portugal’. A thematic analysis was performed with IRAMUTEQ software to define and compare the main themes organizing the re-presentation of the Chinese in both newspapers. Results show that in both cases there are three main forms of presenting the Chinese in Portugal, associated with different institutions: a cultural form, highlighting integration through schools, multiculturalism and shared public spaces, such as Martim Moniz square in Lisbon; a judicial form, associating restaurants and shops to food safety inspection and other vigilance institutions, and an economic form, associating positive incentives to IV. A second, more in-depth set of analysis then focused only on articles discussing the Chinese and IV (Público n= 83; Correio da Manhã n= 82) to examine the extent to which the press coverage of this issue is using communicative contents and formats that may be responsible for closing down (rather than opening up) the debate about IV in the Portuguese public sphere (Maeseele & Raeijmaekers, 2017). For this, articles were analyzed regarding length (short-medium-long), type (with-without opinion), actors quoted (homogenous-heterogeneous groups), orientation (predominance of benefits -balanced- predominance of problems), values that justify IV (economic- positive or negative - of citizenship – positive or negative). The analysis shows that IV are not presented as controversial or problematic. The issue is framed as consensual, and voices presented as homogenous, i.e., making contestation and its values invisible. These results suggest that although we are witnessing a transformation of the values that bound citizenship (to a spatially-driven citizenship, linked to work and permanence is now added an investment-based one), the press is neither stimulating a debate about it in the public sphere, neither offering space to the conflict that may perhaps already exist.